USEFULNESS OF FOREHEAD INFRARED THERMOMETERS TO SCREEN PATIENTS FOR FEVER DURING COVID-19 PANDEMIC - Khan, Nauman Sarir; Arshad, Abdul Rehman; Tariq, Muhammad; Khan, Maqsood; Siddique, Muhammad Bilal; Shabbir, Khawar (Pakistan Armed Forces Medical Journal, 2020)
Objective:To determine accuracy of infrared thermometer for detection of fever as compared to mercury thermometer.Study Design: Cross sectional study.Place andDuration of Study: Department of Medicine, Combined Military Hospital Peshawar, fromMaytoJun 2020.Methodology: All willing adult patients reporting to the fever desk were selected by consecutivesampling. Exclusion criteria included any dermatological condition affecting forehead and unwillingness. Forehead temperature was first checked twice using Kinlee FT3010 infrared thermometer. Axillary temperature was then recorded using a standard clinical mercury thermometer.Results: There were 538 patients, including 251 (46.65%) males and 287 (53.35%) females, aged 46.76± 12.44 years. Median temperatures recorded with infrared and mercury thermometers were 97.00°F (interquartile range: 95.10-97.80°F)and 98.30°F (interquartile range: 98.00-98.90°F) respectively (p